Pengaruh Penerapan Low Cost Carrier & Brand Image Terhadap Keputusan Penumpang Dalam Pembelian Tiket Pesawat Lion Air Di Bandar Udara Internasional Yogyakarta - Evi Wahyuni Dau; Faiz Albana (Lembaga Pengembangan Kinerja Dosen, 2023)
Maskapai Lion Air is a private company engaged in aviation services that have been long enough in the territory of Indonesia. . Lion Air itself is famous for airlines that offer flights with low fares or Low Cost Carier (LCC) at prices that are somewhat cheaper than prices offered by other airlines considered an effort to discipline the public in traveling effectively and efficiently. Brand image is a very important thing that must be considered by companies as market participants, because through a good Brand Image will be able to cause emotional values in consumers. This study used quantitative methods using purposive sampling. The sample used in this study was 100 respondents. The results of the distribution of questionnaires to 100 respondents of Lion Air airline passengers at Bandar Uadar Internasional Yogyakarta and measured using Roscoe theory. Data collection of the number of samples using surveys and instruments in the form of questionnaires. Test T and coefficient of determination with Low Cost Carrier &; Brand Image as the independent variable and Purchase Decision as the bound variable processed using SPSS. The results showed that the value of t calculated t table with a value of 5.326 1.661 with a significance level of 0.05, so it can be concluded that Ho is accepted and Ha is rejected which means there is an influence of Loc Cost Carrier &; Brand Image on Purchasing Decisions simultaneously. based on the coefficient of determination R2, it can be concluded that the contribution of the magnitude of the influence of all variables (Low Cost Carrier &; Brand Image) on the dependent variable (Purchase Decision) is 53.3%, while the remaining 46.7% is influenced by other variables that are not studied. Based on the conclusions obtained in this study, there are several suggestions that can be given regarding Low Cost Carrier &; Brand Image on passenger decisions in purchasing Lion Air flight tickets at Yogyakarta International Airport, for companies it is expected to be able to maintain and improve the image of the company. By continuing to provide and improve quality in serving passenger needs. The company is also expected to understand the characteristics of its consumers about what is needed and wanted, thus the company will be easier in attracting consumers in making purchases both old consumers and to attract new consumers.